The Influence of Service Features and Security on Digital Wallet Usage on MSMEs in Tangerang - Mulyadi, Kharis; Muhyidin, Ayi (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
The current era of digitalization has encouraged the development of technology in the financial services business sector. One form of technological development is financial technology (Fintech). Fintech has changed the conventional business system to digitalization. The purpose of this study was to determine the effect of service features and security on the use of digital wallets (Go-Pay) in MSMEs in Tangerang. This study uses a quantitative approach. The population in this study is MSMEs in Tangerang that use Digital Wallets (Go-Pay) whose number is not known with certainty. The sampling formula used was the Lameslow formula and obtained a sample size of 96. The data analysis technique used was multiple linear regression. The results show that (1) Service Features have a positive and significant effect on the Use of Digital Wallets (Go-Pay), as evidenced by the value of t Count > t Table (4.178 > 1.661) with a significance (0.000 < 0.05). (2) Security has a positive and significant effect on the Use of Digital Wallets (Go-Pay), as evidenced by the value of t Count > t Table (2.331 > 1.661) with a significance (0.000 < 0.05) and (3) Service and Security Features have a positive and positive effect. significantly to the Use of Digital Wallets (Go-Pay), as evidenced by the value of F count > F Table (41.771 > 3.09) with a significance of (0.000 < 0.05). Service and Security Features affect the Use of Digital Wallets (Go-Pay) by 47.3%, the remaining 52.7% is influenced by other variables. With multiple linear regression equation value Y=9,447 + 0,491X1 + 0,261X2.